1994
DOI: 10.1152/ajplung.1994.266.5.l536
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PDE isozymes in human pulmonary artery and effect of selective PDE inhibitors

Abstract: The effects of the nonselective phosphodiesterase (PDE) inhibitor 3-isobutyl-1-methylxanthine (IBMX) and the selective PDE inhibitors motapizone (type III), rolipram (type IV), zardaverine (type III/IV), and zaprinast (type V and I) on prostaglandin F2 alpha (PFG2 alpha)-induced tone in human pulmonary arteries was investigated. Relaxation was achieved by IBMX [concentration eliciting 50% of maximum response (EC50): 11.3 microM, n = 10], motapizone (EC50:3.0 microM, n = 7), zardaverine (EC50: 3.2 microM, n = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
2
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 0 publications
4
142
2
2
Order By: Relevance
“…, respectively, for cGMP and cAMP) are much higher than those previously reported in bovine or human pulmonary arteries (Rabe et al, 1994;Pauvert et al, 2002). Sildenafil inhibited the cGMP-PDE activity in both subcellular fractions.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…, respectively, for cGMP and cAMP) are much higher than those previously reported in bovine or human pulmonary arteries (Rabe et al, 1994;Pauvert et al, 2002). Sildenafil inhibited the cGMP-PDE activity in both subcellular fractions.…”
contrasting
confidence: 52%
“…This pathophysiological adaptation of the pulmonary circulation to maintain hypoxia is a complicated process for which no curative treatment, except heart -lung transplantation, is currently available. Since PDEs are present in the pulmonary artery wall (Rabe et al, 1994;Maclean et al, 1997) and that cGMP-PDE activity is mainly because of the action of PDE5 (Rabe et al, 1994), some PDE5 inhibitors have been administered to counteract PAHT development both in animals and human (Eddahibi et al, 1998;Ziegler et al, 1998;Hanasato et al, 1999). Very recently, pioneer clinical trials with sildenafil have been performed in PAHT (Abrams et al, 2000;Ichinose et al, 2001;Zhao et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the human pulmonary circulation, the isoforms 1, 3, 4, and 5 seem to be involved in regulating pulmonary resistance. 10,11 A peculiarity of the cAMP-hydrolyzing PDE 3 is that it can be inhibited by cGMP. 2,12 Therefore, in tissues containing both PDE 3 and 5, sildenafil could indirectly increase cAMP concentrations via inhibition of PDE 3 by cGMP ( Figure 1).…”
Section: Selectivity Of Pde 5 Inhibitors and Tissue Distribution Of Pmentioning
confidence: 99%
“…10,11 Thus, the blood pressure-lowering effects of sildenafil in the pulmonary circulation are of special interest. Zhao et al 48 demonstrated that 100 mg of oral sildenafil markedly reduced the rise in arterial pulmonary pressure in response to breathing 11% inspiratory oxygen in healthy volunteers, which paralleled their findings in a mouse model of hypoxia-induced pulmonary hypertension.…”
Section: Effects Of Pde 5 Inhibition On Pulmonary Vasculaturementioning
confidence: 99%
“…This is the predominant phosphodiesterase isoform in the lungs (Rabe et al 1994). Sildenafi l inhibits the breakdown of cGMP, and enhances the ability of endothelial nitric oxide to vasodilate the pulmonary arteries, reducing intravascular calcium, relaxing smooth muscle cells and reducing pulmonary vascular resistance (PVR) (Corbin et al 1999).…”
Section: Introductionmentioning
confidence: 99%